Olive Germplasm Italian Catalogue of Olive Varieties - Muzzalupo, Innocenzo (IntechOpen, 2012)
The olive (Olea europaea) is increasingly recognized as a crop of great economic and health importance world-wide. Olive growing in Italy is very important, but there is still a high degree of confusion regarding the genetic identity of cultivars. This book is a source of recently accumulated information on olive trees and on olive oil industry. The objective of this book is to provide knowledge which is appropriate for students, scientists, both experienced and inexperienced horticulturists and, in general, for anyone wishing to acquire knowledge and experience of olive cultivation to increase productivity and improve product quality. The book is divided into two parts: I) the olive cultivation, table olive and olive oil industry in Italy and II) Italian catalogue of olive varieties. All chapters have been written by renowned professionals working on olive cultivation, table olives and olive oil production and related disciplines. Part I covers all aspects of olive fruit production, from site selection, recommended varieties, pest and disease control, to primary and secondary processing. Part II contains the chapter on the description of Italian olive varieties. It is well illustrated and includes 200 elaiographic cards with colour photos, graphs and tables.